Role of Community-level Health Behaviors and Social Determinants of Health in Preventable Hospitalizations - Elizabeth Ayangunna; Kingsley Kalu; Gulzar Shah (Georgia Southern University, 2022)
Background Hospitalizations contribute significantly to the country's health expenditures. There are factors in addition to clinical care that determines whether a community can prevent hospitalizations from certain medical conditions. Purpose The purpose of this paper is to explain the role of community-level health behaviors and social determinants of health (SDoH) in preventable hospitalizations. Methods This study used secondary data from the 2021 County Health Rankings for 8 states in HHS Region 4--Georgia, Florida, North Carolina, South Carolina, Alabama, Mississippi, Florida, and Tennessee. Descriptive analyses and multivariate linear regression were computed to examine the association between the dependent variable- preventable hospitalizations and independent variables operationalizing community health behaviors and SDoH at the county level. Results The results show that higher percentages of adult smokers and obese adults at the county level were associated with increased hospitalizations while higher county-level percentages of Medicare enrollees with flu vaccinations, access to exercise opportunities, and primary care physician rate could reduce preventable hospitalizations. After controlling for age, gender, and race, only higher percentages of adult smokers and Medicare enrollees with flu vaccinations were significant predictors of preventable hospitalizations. Conclusion Community-level determinants of health may be better predictors of preventable hospitalizations than individual and clinical factors. This indicates that community-level health promotion activities (e.g. encouraging flu vaccination) must be part of the interventions attempting to reduce preventable hospitalizations and in turn the burden on healthcare systems. Primary care providers and public health officials need to collaborate and develop innovative population health solutions to reduce inpatient hospitalizations for ambulatory care sensitive conditions.